Comprehensive harmonic performance of MPPT-integrated SPWM controlled PV-fed multilevel inverter - Swapna Subudhiray; Smrutiranjan Nayak; Priyattama Moharana (Bulletin of Electrical Engineering and Informatics, 2026)
This paper presents a comprehensive harmonic performance and robustness evaluation of a photovoltaic (PV)-fed cascaded H-bridge multilevel inverter (CHB-MLI) integrated with a perturb and observe (P&O) maximum power point tracking (MPPT) algorithm. The proposed inverter is controlled using sinusoidal pulse width modulation (SPWM) to produce a high-quality AC output suitable for renewable energy applications. An inductor–capacitor (LC) filter is incorporated to reduce switching harmonics and improve output voltage quality. Harmonic analysis indicates that the total harmonic distortion (THD) of the inverter output voltage is reduced from 17.40% to 3.50% after filtering, which satisfies the IEEE 519 standard for low-voltage systems. Furthermore, a comparative evaluation with selective harmonic elimination (SHE) and space vector pulse width modulation (SVPWM) techniques highlights that SPWM provides a practical trade-off between harmonic performance and implementation complexity. The results confirm that the proposed PV-fed multilevel inverter (MLI) architecture offers reliable and efficient performance for renewable energy applications.